0484 How Much Improvement in Subject-Reported Sleep Onset Latency is Needed for Patients to Report a Positive Impact of Their Insomnia Medication?. (27th May 2020) - Drake, C; Yardley, J; Pinner, K; Perdomo, C; Kumar, D; Moline, M
Abstract: Introduction: How much improvement would be considered meaningful from the patient perspective is not well defined. In SUNRISE-2 (NCT02952820; E2006-G000-303), using the Patient Global Impression-Insomnia version (PGI-I), subjects rated how treatment impacted subjective (sleep diary-based) sleep onset latency (sSOL; Question2; positive, neutral, and negative) relative to before starting treatment. Meaningful change can thus be determined based on the change from baseline (CFB) in subjects with a positive score. Methods: SUNRISE-2 (n=949, full analysis set) was a Phase 3, 12-month, double-blind, global study in subjects age ≥18y with insomnia disorder. Subjects received PBO (N=318), LEM 5mg (LEM5, N=316) or LEM 10mg (LEM10, N=315) for 6 months. At the end of Month 6, PBO subjects were rerandomized to LEM5 or LEM10; LEM5 and LEM10 subjects continued at the same dose for 6 more months. The ranges of median CFB in sSOL (minutes) at 6 months were examined in response to PGI-I Item 2. Results: At 6 months, subjects reporting positive medication effect (PBO, n=110; LEM5, n=178; LEM10, n=159) showed median CFB in sSOL from -17.5 to -32.1 minutes across treatment groups. In subjects reporting neutral effect (PBO, n=49; LEM5, n=28; LEM10, n=27), median CFB in sSOL ranged from -10.4 to -25.6 minutes across treatment groups. In subjects reporting negative medication effect (PBO, n=82; LEM5, n=34; LEM10, n=32), median CFB in sSOL ranged from -8.6 to -10.4 minutes across treatment groups. The PBO group provided the smallest numbers for each response category range. Conclusion: Subjects reporting positive medication effect on PGI-I Item 2, i.e. decreased time to fall asleep, had corresponding changes from baseline in sSOL ranging from -17.5 to -32.1 minutes. Thus, this range may represent a clinically meaningful improvement as perceived by patient-subjects, and may be useful to clinicians in determining whether a treatment regimen is working for their patients. Support: Eisai Inc.